THU0719-HPR THE PATIENT ACTIVATION MEASURE (PAM): WHAT DO PATIENTS WITH RHEUMATIC CONDITIONS THINK ABOUT IT?. (June 2019) - Jones, Bethan; Hunt, Andrew; Harcourt, Diana; Hewlett, Sarah; Dures, Emma
Abstract : Background: Patient activation describes the skills, abilities and confidence someone has to actively manage their health. The most common way of capturing patient activation is by using the Patient Activation Measure (PAM), and the NHS has begun to integrate use of the measure into services as an outcome measure or as a tool to tailor care. The PAM has been widely adopted and used in a variety of populations both within the NHS and internationally, but case studies have reported that some patients found that the PAM was too broad to capture the skills they used to manage their health. There has been limited research gathering patients' perceptions of the suitability and acceptability of the PAM, particularly within a rheumatology context. Objectives: To gather participants' opinions on the PAM as a method of capturing patient activation. Methods: Seventeen participants living with a rheumatic condition in the South West of England participated in semi-structured interviews as part of a wider qualitative study investigating perceptions of patient activation. Participants completed the PAM at the beginning of the interview. In the last phase of the interview, they were asked to review and reflect on the PAM, including individual survey items and how closely they matched their experiences. Relevant sections of the interviews were analysed iteratively and participants' perspectives were grouped into themes. Results: Participants' feedback on the PAM ranged, and some participants reported that the PAM entirely captured how they perceived patient activation and the way that they managed their conditions. However, this was not the case for all participants. Aspects of the PAM that participants felt were not sufficiently recognised included how they managed the psychological impact of their condition, and how they discussed their condition with loved ones. Participants commonly reported that they thought the phrasing of certain PAM items did not match the lived experience of their conditions. For example, PAM items capturing how well patients could prevent further problems was identified as a challenge for participants living with a fluctuating condition, and participants commented that the PAM does not check from where participants received or sought this information. The distinction between whether patients independently researched information about diagnoses and medications or received this passively from healthcare professionals also appeared important to some participants, as well as whether this information was accurate. Conclusion: The PAM survey is generally considered a reliable and valid measure of patient activation, but there may be aspects of it that do not capture the realities of living with a long-term fluctuating condition. Rather than a stand-alone measure, the PAM would be best used in conjunction with healthcare professionals' clinical judgement to capture peoples' understanding of their conditions and how well they are able to recognise and respond to flare-ups and fluctuations. Acknowledgement: This work was funded by a PhD scholarship by Versus Arthritis (Grant Number 20971). Disclosure of Interests: Bethan Jones: None declared, Andrew Hunt: None declared, Diana Harcourt: None declared, Sarah Hewlett Grant/research support from: Has previously received an independent learning grant from Pfizer, however the work has been completed and the grant has been closed., Emma Dures Grant/research support from: Has previously received an independent learning grant from Pfizer, however the work has been completed and the grant has been closed.